A case of pemphigus vulgaris in a patient with abdominal tumor as collaborative disease - Prima Sanjiwani Saraswati Sudarsa; Marvin Giantoro; Luh Gede Melia Puspita Sari; I Made Setiadji (Explorer Front, 2022)
Background: Pemphigus is an autoimmune disease with clinical manifestations of chronic intraepidermal bullae on the skin, mucosa, and loose walls.Pemphigus can be categorized into four types, namely pemphigus vulgaris (PV), pemphigus vegetans, pemphigus foliaceus, and paraneoplastic pemphigus. Pemphigus vulgaris is the most common form of with the highest epidemiology. Pemphigus vulgaris with abdominal tumors cannot be associated where abdominal tumors do not trigger the occurrence of PV. However, abdominal tumors can increase morbidity and provide poor prognosis. Case Description: A male, 46 years old, Balinese, Indonesian, came to the Sanglah Hospital Emergency Room with the chief complaint of painful sores around the body, hands, and feet since 20 days ago. Initially the patient said that there were loose, watery blister filled with serous fluid, which after a few days burst and left sores. The blister start on the feet and then spread to the hands and body. The patient was diagnosed with pemphigus vulgaris and abdominal tumors by the digestive surgery doctor. The patient had never had a similar complaint before. History of applying oil, traditional ingredients and topical drugs was denied. The patient was treated mainly with methylprednisolone and showed clinical improvement. Conclusion: We report a case of PV in a 46-year-old man with abdominal tumors. This case report is expected to add insight on how to diagnose PV, how to determine therapy, the wound healing process, how to treat wounds, prevent disease expansion, and the relationship between abdominal tumors and PV.